A polymorphism in the gene for microsomal epoxide hydrolase is associated with pre-eclampsia. Issue 4 (1st April 2001) - Zusterzeel, Petra L M; Peters, Wilbert H M; Visser, Willy; Hermsen, Kristel J M; Roelofs, Hennie M J; Steegers, Eric A P
Abstract : OBJECTIVE: Microsomal epoxide hydrolase is an important enzyme involved in the metabolism of endogenous and exogenous toxicants. Polymorphic variants of the human epoxide hydrolase gene vary in enzyme activity. We determined whether genetic variability in the gene encoding for microsomal epoxide hydrolase contributes to individual differences in susceptibility to the development of pre-eclampsia with or without the syndrome of Haemolysis, Elevated Liver enzymes, and Low Platelets (HELLP). METHODS: A total of 183 non-pregnant women with a history of pre-eclampsia, 96 of whom had concurrently developed the HELLP syndrome, and 151 healthy female controls were genotyped for the 113Tyr→His polymorphism in exon 3 and the 139His→Arg polymorphism in exon 4 of the epoxide hydrolase gene by a polymerase chain reaction-restriction fragment length polymorphism assay. Chi-square analysis was used for statistical evaluation of differences in polymorphic rates. RESULTS: In pre-eclampsia a higher frequency (29%) of the high activity genotype Tyr113 Tyr113 in exon 3 was found as compared to controls (16%, OR 2.0, 95% CI 1.2-3.7). There was no difference between groups for the 139His→Arg polymorphism. In women with a history of pre-eclampsia, no difference in epoxide hydrolase genotypes was found between women who either did or did not develop the HELLP syndrome. In addition, a significant association was found between predicted EPHX activity and pre-eclampsia. CONCLUSIONS: Women with the high activity genotype in exon 3, which could reflect differences in metabolic activation of endogenous or exogenous toxic compounds, may have enhanced susceptibility to pre-eclampsia. However, polymorphisms in the epoxide hydrolase gene do not seem to influence the risk for concurrent development of the HELLP syndrome.